THE EFFECTIVENESS OF NEWSELA ONLINE BLOGS IN TEACHING STUDENTS READING COMPERHENSION ON EXPLANATION TEXTS: A CASE OF THE 10TH GRADE OF SMA NEGERI 1 TAYU - Putri Eka Andriani; Rahmawati Sukmaningrum; Sri Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to find out the effectiveness of using Newsela online blogs in teaching students’ reading comprehension. Employing a quasi-experimental approach, the study included two pre- and post-test classes design as the approach for the research. The sample included 36 X-1 students’ and 36 X-2 students’ from SMA Negeri 1 Tayu while the course of the year 2023/2024. Two groups—the experimental and control groups—were established out of the pupils. The data that was gathered was examined using a t-test. As stated in the analysis, the t-test was more valuable than the t table (t count). = 19.630, t table = 2.030 at the meaningful 5% level). Both groups' reading abilities have increased, although there is still a sizable gap between them. The experimental class's average post-test learning performance is 86.94, but the control class's average is 60.55. Consequently, it is feasible to draw the conclusion that by applying the Newsela online blogs is effective in students’ reading skills.